PENGARUH KUALITAS PRODUK, FITUR PRODUK, DESAIN PRODUK TERHADAP MINAT BELI KONSUMEN PADA CENTRO MEUBEL DI KABUPATEN SITUBONDO - Moh Faizi; Hardjono Hardjono; Riska Ayu Pramesthi (Fakultas Ekonomi dan Bisnis, 2026)
This study aims (1) to determine the partial effect of product quality, product features and product design on consumer buying interest (2) to determine the simultaneous effect of product quality, product features and product design on consumer purchase interest (3) to determine product quality. , product features and product design that have a dominant effect on consumer buying interest. The data obtained were analyzed using statistical formulas, namely by using multiple linear regression analysis, t test, F test, and coefficient of determination. The results of the study were multiple linear regression equation Y = 3.651E-17 + 0.020X1 + 0.007X2 + 0.955X3 + 0.031 . The result of t test for product quality variable t count 3.551> t table 1.986, product feature variable t count 2.205> t table 1.986, product design variable t count 30.520> t table 1.986 so it can be concluded that product quality, product features and product design partially influence (Y). The value of Fcount> Ftable, 313.776> 2.70, so it can be concluded that product quality, product features and product design simultaneously influence consumer purchase interest. The dominant test for the product design variable is 30.520, which is said to be the most dominant.s 30.520, which is said to be the most dominant.